Penerapan Model Game-Based Learning Media Wordwall untuk Meningkatkan Hasil Belajar Peserta Didik (Penelitian Tindakan Kelas di Kelas VII-A SMP Negeri 12 Bandung): Penelitian - Nadila Oktavianing; Aim Abdulkarim; Pitria Sopianingsih (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is motivated by the problem of low student learning outcomes in Pancasila education subjects in class VII-A of SMP Negeri 12 Bandung. Based on initial observations, student responses to teachers are still lacking, assignments given are still ignored by some students, less interesting, and the results of the Final Semester Summative Assessment have not met the KKM 75. To overcome these problems, more interesting and innovative learning is needed through Wordwall game-based learning media. Researchers used a mix method approach, with the Classroom Action Research method. Data collection through observation, interviews, pre-tests, post-tests, questionnaires. Data analysis through reduction, data presentation, drawing conclusions, triangulation of data validation, and member checks. The results of the study showed an increase in student learning outcomes, through the post-test completion of cycle I as many as 11 people, cycle II 31 people, cycle III 34 people.